2013
DOI: 10.1590/s2176-94512013000200021
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary incisor retraction: evaluation of different mechanisms

Abstract: Objective:To mechanically evaluate different systems used for incisors retraction. Methods: Three different methods for incisors retraction using 0.019 x 0.025-in stainless steel wire were evaluated. The samples were divided into three groups: Group A (retraction arch with 7-mm high vertical hooks); Group G3 (elastic chain attached to the miniimplant and to the 3-mm stainless steel hook soldered to the retraction arch); Group G6 (elastic chain attached to the mini-implant and to the 6-mm stainless steel hook s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Consequently, retraction of incisors result in uprighting and relative extrusion as the crown was retracted below the center of rotation (Kuhlberg and Nanda, 2005). The same extrusive effect was also seen with sliding mechanics; as incisors are pulled below the center of rotation, and torque loss occur (Jayaratne et al, 2017;Ruellas et al, 2013). This extrusive movement results in worsening any deep bite present before retraction, and maxillary or mandibular incisors should be intruded to compensate this effect.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, retraction of incisors result in uprighting and relative extrusion as the crown was retracted below the center of rotation (Kuhlberg and Nanda, 2005). The same extrusive effect was also seen with sliding mechanics; as incisors are pulled below the center of rotation, and torque loss occur (Jayaratne et al, 2017;Ruellas et al, 2013). This extrusive movement results in worsening any deep bite present before retraction, and maxillary or mandibular incisors should be intruded to compensate this effect.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This finding is contradicted by many authors, who reported that intrusion is most likely to be a risk factor for root resorption when compared to extrusion; intrusion of teeth causes about four times more root resorption than extrusion (Han et al, 2005;Parker and Harris, 1998). This finding can be justified because the extractions of premolars, space closure, and retractions of incisors result in controlled and uncontrolled tipping of these teeth, which affect the incisors angulation and have extrusive forces (Jayaratne et al, 2017;Luiz et al, 2016;Ruellas et al, 2013;Sarver and Weissman, 1995). In Orthodontics department, Marmara University, two space closure mechanics are applied; sliding mechanics and closing loops.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Anterior teeth were retracted sequentially; A force of 100-g was applied to retract maxillary canine by Ni-Ti closed coil spring ligated with a wire to the canine bracket hook [15] . After canine retraction, the maxillary incisors were retracted by 130-g force using Ni-Ti closed coil spring extending from the hook of the buccal tube on the first molar band to helices placed distal to lateral incisors [16] (Figure 2).…”
Section: Interventionsmentioning
confidence: 99%
“… 10 This action requires full-size archwires to avoid play between the archwire and the slot walls. 11 , 12 However, archwire of a round cross-section is the standard choice for initial leveling and alignment. 13 Round archwires produce tipping movement, thus changing crown inclination, which may be or may not be desired.…”
Section: Introductionmentioning
confidence: 99%